PENGEMBANGAN EDIBLE FILM DENGAN MENGGUNAKAN PATI GANYONG TERMODIFIKASI IKATAN SILANG [Development of Edible Film by Using Modified Cross-Linking Ganyong Starch] - Budi Santoso; Filli Pratama; Basuni Hamzah; Rindit Pambayun (Jurnal Teknologi dan Industri Pangan, 2011)
The objective of the research was to study chemical and physical characteristics of edible film of modified ganyong starch. The first step of the research was to make modified ganyong starch with cross linking method by using POCl3. The second step is to make edible film from modified ganyong starch. The results showed that the phosphate content and value of substitution degree of modified ganyong starch increased, but its amylose and starch content decreased. Edible film made of ganyong starch modified with POCl3 0.08% had the lowest water vapor transmission rate (18.25+0,003 g.m-2.day-1) and percentage elongation (17.01+0,001%), but the highest puncture strength (146.89+0.001 gf).